Optimasi Organizational Citizenship Behaviour (OCB) Guru Sekolah Menengah Kejuruan (SMK) Melalui Penguatan Knowledge Management, Kecerdasan Adversitas, Efikasi Diri, Budaya Organisasi dan Motivasi Kerja - Andi Hermawan; Briliantina Indrati; Mamah Siti Rohmah (Syntax Corporation Indonesia, 2023)
Teachers who successfully carry out their main duties as stated in their job descriptions plus the awareness of doing something extra are the key to organizational success. Extra activities that are not directly related to the formal reward system in place are called OCB (Organizational Citizenship Behavior). Based on preliminary research, it is known that permanent foundation teachers (GTY) of PGRI Vocational High Schools (SMK) in Bogor Regency have relatively low OCB. Therefore, research is needed to obtain information on variables related to increasing OCB. The aim of this research is to make efforts to increase vocational school teachers' OCB by conducting research on the influence of knowledge management variables, self-efficacy adversity intelligence, organizational culture and work motivation. This research uses the path analysis method to determine the influence between the variables studied and the SITOREM method for indicator analysis in order to obtain optimal solutions in efforts to increase vocational school teachers' OCB.